Improving Students’ Reading Skill Through Think-Pair-Share (TPS) Technique - Muhammad Hudri; H Irwandi (Universitas Muhammadiyah Mataram, 2018)
This study aims to investigate how the Think-Pair-Share (TPS) technique can improve the students’ reading skill at English Language Department, Muhammadiyah University of Mataram. The problem found in the fourth semester students is that they have low ability in comprehending the text. The TPS technique is offered by the researcher to solve the problem. Later on, the design of this research was classroom action research adopted from Kemmis & McTaggart which goes through a cycle that consists of four stages namely planning, acting, observing, and reflecting. At the cycle 1 the students failed to meet the criteria of success because only 14 (fourteen) out of 30 (thirty) or 47% students who got the minimum passing grade 75 (seventy five) and the average score was 67. It meant that the study must be continued to the next cycle. At last, in the cycle 2 met the criteria of success in which 67% students or 20 (twenty) out of 30 (thirty) students met the minimum passing grade 75 and the average score was 72. Besides gaining improvement in the reading score, the students also seemed enthusiastic in thinking, pairing and sharing their ideas. They stated that this technique is able to encourage and motivate them in thinking, exploring and sharing their opinion and ideas. This technique is also good to enhance the cooperation with other people. Finally, TPS technique is also able to increase the students’ confidence to share their ideas in front of many people.